Analysis Of Online Begging Phenomena in Tiktok (Case Study of Changes in the Structure of Social Problems About Online Beggars) - Raisha Shahana; Maria Indriani K; Detya Wiryany (Westscience Press, 2023)
This article focuses on social media TikTok so that it can have a negative impact on society, such as the emergence of the phenomenon of